Alteration in intraepitheliallymphocyte-natural killer (IEL-NK) cell populations following infection with differrnt strains of Newcastle disease virus - Abdolmaleki, Mostafa; Tan, Sheau Wei; Yeap, Swee Keong; Satharasinghe, Dilan Amila; Jahromi, Mohammad Zareian; Omar, Abdul Rahman; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Newcastle disease (ND) is highly contagious disease that can caused high mortality up to 100% in susceptible chickens. Although antibody response is the main immune response that confers protection, the involvement of cell-mediated immunity is not clear. Similar to mammals, chickens also have Natural Killer (NK) cells which were first described in 1975 as cytotoxic lymphocytes and they play an important role in the early defense against viruses. They have been widely investigated in various mammalian species, but their role in chicken is poorly understood. Here, we isolated and examined intestinal intra-epithelial lymphocytes (IEL) NK cells population changes following infection with velogenic genotype VIII and LaSota vaccine strain. Flow cytometry analysis indicated that the IEL-NK cells population of chickens infected with velogenic genotype VIII NDV was significant decreased compared to LaSota and control groups.